DYNAMICS OF CHANGES IN BIOCHEMICAL MARKERS OF BLOOD SERUM AFTER REMOVAL OF MANDIBULAR MOLARS AND AUGMENTATION OF THE ALVEOLAR PROCESS - Kolesnichenko, M.O.; Savchenko, D.V.; Savchenko, V.V.; Ivaniuk, O.S.; Zhyvotovskyi, I.V.; Yacenko, P.I.; Lokes, K.P. (World of Medicine and Biology, 2023)
The article describes the dynamics of connective tissue markers in blood serum (glycoproteins and chondroitin sulfates) under the conditions of mandibular molars extraction and augmentation of the alveolar process. According to the obtained data, it was established that the operation of tooth extraction and augmentation of the bone defect of the alveolar process of mandible caused more significant changes in the content of blood serum glycoproteins than chondroitin sulfates. The minimal changes in the studied parameters were observed in the second experimental group (when augmentation of the bone defect of the mandibular alveolar process with bone substitute of animal origin granules in combination with keratoxenoimplantant was performed after the molar extraction), the most significant changes were noted in the control group, in which no augmentation of the alveolar process was performed at all.